Space use variation in Co-occurring sister species: Response to environmental variation or competition? - Dufour, C.M.S.; Meynard, C.; Watson, J.; Pillay, N.; Ganem, G.; Rioux, C.; Benhamou, S.; Perez, J.; Du Plessis, J.J.; Avenant, N. (Public Library of Science, 2015)
Coexistence often involves niche differentiation either as the result of environmental divergence, or in response to competition. Disentangling the causes of such divergence requires that environmental variation across space is taken into account, which is rarely done in empirical studies. We address the role of environmental variation versus competition in coexistence between two rodent species: Rhabdomys bechuanae (bechuanae) and Rhabdomys dilectus dilectus (dilectus) comparing their habitat preference and home range (HR) size in areas with similar climates, where their distributions abut (allopatry) or overlap (sympatry). Using Outlying Mean Index analyses, we test whether habitat characteristics of the species deviate significantly from a random sample of available habitats. In allopatry, results suggest habitat selection: dilectus preferring grasslands with little bare soil while bechuanae occurring in open shrublands. In sympatry, shrubland type habitats dominate and differences are less marked, yet dilectus selects habitats with more cover than bechuanae. Interestingly, bechuanae shows larger HRs than dilectus, and both species display larger HRs in sympatry. Further, HR overlaps between species are lower than expected. We discuss our results in light of data on the phylogeography of the genus and propose that evolution in allopatry resulted in adaptation leading to different habitat preferences, even at their distribution margins, a divergence expected to facilitate coexistence. However, since sympatry occurs in sites where environmental characteristics do not allow complete species separation, competition may explain reduced inter-species overlap and character displacement in HR size. This study reveals that both environmental variation and competition may shape species coexistence.
Keywords: adult; allopartry; animal behavior; animal experiment; controlled study; ecological niche; environmental aspects and related phenomena; environmental variation; habitat selection; habitat use; home range; intraspecific competition; mouse; nonhuman; phylogeography; Rhabdomys bechuanae; Rhabdomys dilectus; rodent; species coexistence; species comparison; species differentiation; sympatry; Rhabdomys; Rodentia